Entraves na utilização de sistemas de informação do gerenciamento de projetos em empresas da construção civil no estado de Sergipe - Silva, Alexandre de Oliveira (2020)
Construction Industry tends to manage its operations via projects and represents between eight and nine per cent of Brazilian Gross Domestic Product, being the industry a driver for the economic development in the country. Thus, it is paramount that this industry continues seeking technological innovations and methodologies that enable them to execute their enterprises and overcome the triple restriction of time, cost, and quality. Among all available technologies, Project Management Information Systems (PMIS) can be highlighted since they have the potential of integrating all Project Management Knowledge and activity areas. Nevertheless, despite their potential, PMIS still have not demonstrated to be sufficientlypresent to carry out this role in the construction industry. Notwithstanding, the objective of this study is to evaluate which are the main difficulties to PMIS utilization in private construction companies in the State of Sergipe. Research also presents PMIS benefits and functionalities, identifies their utilization in different sizes of civil construction companies and characterizes project management maturity in the evaluated enterprises. As for methodology, present research has a quantitative and qualitative nature and is characterized as exploratory and descriptive. Research was performed by means of a literature review on project management, PMIS and maturity models. From the study of these models it was possible to understand that, for the correct utilization of a complex information system such as a PMIS, some pre-conditions must be present in the organization. These conditions can be evaluated with the use of maturity models and, among many of them, PRADO-MMGP (2015) was selected for having national historical data on top ofpresenting similarities to models which are internationally accepted. This, enterprises from the Brazilian State of Sergipe were invited to a Project Management Maturity survey and thirty-three of them effectively responded. Survey analysis demonstrated that few of the respondent companies presented adequate characteristics to the full utilization of PMIS. These companies had high maturity levels and were adherent mainly to the dimensions project management methodologies and informatization. Ten companies from the State of Sergipe presented maturity levels starting from three in a scale from one to five, and were considered, therefore, to be part of the multiple cases study. All these companies were invited and five of them participated in the study. From there onwards, semi-structured interviews and information triangulation were done with the survey and the theoretical review to understand which are the restrictions for the utilization of PMIS. In the multiple cases study many difficulties were identified for the utilization of such technologies, among them: deficiencies in the standardization and project management methodologies, lack of uniformity in understanding the systems, resistance to utilize, resources and organization structure difficulties, besides system’s quality issues: PMIS system, information and service quality which compromise frontally the diffusion and utilization in scale for this technology in the civil construction industry.